Approach to overgrowth syndromes in the genome era. Issue 4 (2nd December 2019) - Burkardt, Deepika D.; Tatton‐Brown, Katrina; Dobyns, William; Graham, John M.
Abstract: This introduction to the special issue of AJMG Part C : Overgrowth Syndromes updates the current understanding of overgrowth syndromes. We clarify the terminology associated with overgrowth, review some common pathways to overgrowth and present a preliminary classification based on currently known genomic and epigenetic mechanisms. We introduce the articles of this issue—new research and reviews of well‐established and recently described overgrowth syndromes of the brain, body or both.